2D/3D NOVEL MATERIALS FOR HIGH PERFORMANCE PEROVSKITE SOLAR CELLS - Aidarkhanov, Damir (Nazarbayev University School of Engineering and Digital Sciences, 2022)
The continuous increase of energy demand and emission of greenhouse gases from the conventional fossil fuels signifies the importance of renewable energy. The solar radiation is a readily available renewable energy source. If the amount of solar energy irradiated on the earth can be converted into electrical energy very efficiently, the energy demand of our daily life can be satisfied. The photovoltaics (i.e. solar cells) are the devices directly converting the solar irradiation into the electrical energy. Among the existing photovoltaic technologies, the metal halide perovskite solar cells (PSCs) demonstrate a huge potential of realizing cost-effective and high-performance devices for future practical applications. The theoretical calculations demonstrate that a single junction PSC can reach a power conversion efficiency (PCE) above 30%. However, there are still a number of challenges hindering the commercialization of PSCs for the practical use. This work focuses on enhancing the performance of PSCs via application of novel 2D/3D materials and engineering of device architectures. A multilayer structure for electron-transporting layer (ETL) has been developed for high performance PSCs. It is shown that a triple-layer ETL consisted of SnO2 quantum dots, SnO2 nanoparticles, and fullerene-derivative based passivation layer can facilitate the carrier transports due to optimization of surface morphology of ETL which yields a better interface quality for subsequently deposited perovskite absorber layer. The defect states residing the interface between the ETL and perovskite are also reduced by optimizing the architecture of ETL in PSCs. Further, a two-dimensional material, black phosphorus (BP) in form of nanoflakes was used to modify the interface between the ETL and the perovskite layer. The application of BP in PSCs demonstrates an increase of the device efficiency and stability. The positive effect introduced by BP is attributed to the improved perovskite crystallization on BP modified ETL and passivation of interfacial defects by lone-pair electrons of BP. Meanwhile, the photovoltaic properties of multiple cations mixed-halide perovskite layer can be improved by incorporation of a cross-linking material, 2,2′-(Ethylenedioxy) bis(ethylammonium iodide). The PSCs incorporated with an optimized concentration of cross-linking material demonstrate an enhancement of PCE and improvement in stability, which are attributed to the passivation of the defect states located at the surface and grain boundaries of perovskite by the cross-linking molecules. The cross linker assisted crystallization also leads to the formation of compact perovskite thin films, which could suppress the penetration of various species such as moisture, oxygen etc. from the atmosphere
Keywords: electron-transporting layer; ETL; type of access: gated access; power conversion efficiency; PCE; energy demand; emission of greenhouse gases; perovskite solar cells; PSCs